Linear porphyrin dimers with fluorenyl arms linked by an ethynyl bridge - Merhi, Areej; Drouet, Samuel; Kerisit, Nicolas; Paul-Roth, Christine O. (Tetrahedron, 2013)
A series of porphyrin monomers bearing fluorenyl donor groups is presented; successively, compounds 10, 11, 12, and 13 bearing three fluorenyl groups. Starting from these building blocks, the synthesis of new porphyrin ethynyl-linked dimers 7 and 8, bearing in totally six peripheral fluorenyl arms is attempted. Dimers are obtained by coupling two porphyrin monomers, using a palladium catalyst, by a rigid bridge. Luminescence studies of new dimers 7 and 8 are presented. We can then compare the detailed luminescence properties of these dimers with former porphyrin monomer possessing four fluorenyl arms TFP (2), which is the precursor model of this work, to porphyrin dendrimers bearing various numbers of fluorenyl arms (3 and 4) and finally to corresponding supramolecular assemblies (5 and 6). [Display omitted]